2016
DOI: 10.1111/acel.12540
|View full text |Cite
|
Sign up to set email alerts
|

Activated monocytes resist elimination by retinal pigment epithelium and downregulate their OTX2 expression via TNF‐α

Abstract: SummaryOrthodenticle homeobox 2 (OTX2) controls essential, homeostatic retinal pigment epithelial (RPE) genes in the adult. Using cocultures of human CD14+ blood monocytes (Mos) and primary porcine RPE cells and a fully humanized system using human‐induced pluripotent stem cell‐derived RPE cells, we show that activated Mos markedly inhibit RPE OTX2 expression and resist elimination in contact with the immunosuppressive RPE. Mechanistically, we demonstrate that TNF‐α, secreted from activated Mos, mediates the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 32 publications
1
48
0
Order By: Relevance
“…It has also been reported that ARMS2/HTRA1 polymorphism leads to compromized SOD2 response , while knockout of SOD2 in mice is used as an early model of AMD . APOE , a transporter of lipoproteins and fat‐soluble vitamins, and tumor necrosis factor ( TNF ) ‐α , a cytokine involved in systemic inflammation and implicated in downregulation of orthodenticle homeobox 2 ( OTX2 ) , showed increased expression in high‐risk donors (Fig. G, H); however, interleukin‐18 ( IL18 ), a cytokine that can suppress VEGF expression and has been associated with AMD showed no significant difference between genotypes (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…It has also been reported that ARMS2/HTRA1 polymorphism leads to compromized SOD2 response , while knockout of SOD2 in mice is used as an early model of AMD . APOE , a transporter of lipoproteins and fat‐soluble vitamins, and tumor necrosis factor ( TNF ) ‐α , a cytokine involved in systemic inflammation and implicated in downregulation of orthodenticle homeobox 2 ( OTX2 ) , showed increased expression in high‐risk donors (Fig. G, H); however, interleukin‐18 ( IL18 ), a cytokine that can suppress VEGF expression and has been associated with AMD showed no significant difference between genotypes (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…In response to oxidatively damaged lipids, macrophages polarized toward an M1 phenotype accumulated in the subretinal space of mice immunized with carboxyethylpyrrole (CEP) prior to lesion development while macrophages and an AMD phenotype were absent in Ccr2-deficient mice, implicating macrophages in tissue injury (Cruz-Guilloty et al, 2013). Furthermore, subretinal mononuclear phagocytes or IL-1β might contribute to cone photoreceptor loss late stage AMD (Eandi et al, 2016) in part, because activated mononuclear phagocytes might resist elimination by the RPE with production of TNF-α, which downregulates OTX2, an important transcription factor that regulates genes that are essential to RPE function (Mathis et al, 2017). In the choroid, macrophages are recruited to basal deposits and drusen (Cherepanoff et al, 2010).…”
Section: The Role Of Inflammation On the Rpementioning
confidence: 99%
“…TNFα have a higher prevalence of CNV (Cousins et al, 2004). It also has profound effects on RPE homeostasis as it represses a key transcription factor of the RPE, the orthodenticle homeobox 2 (OTX2) (Mathis et al, 2017). OTX2 is a critical transcription factor for the development of the brain and sensory organs (Acampora et al, 1995;Cantos et al, 2000;Fossat et al, 2006).…”
Section: Tumor Necrosis Factor α (Tnfα)mentioning
confidence: 99%